Another fine mess : a novel - Ryan, Lindy (Ryan, Lindy. Bless your heart (Series), 2025)
"From Lindy Ryan, "one of the "most electrifying voices in the horror genre" (Gwendolyn Kiste), Another Fine Mess brings the Evans women back around in this unputdownable, crackling, rollicking mystery of humor, heart, and horror. Making sure dead things stay buried is the family business ... For over a hundred years, the Evans women have kept the undead in their strange southeast Texas town from rising. But sometimes the dead rise too quick-and that's what left Lenore Evans, and her granddaughter Luna, burying Luna's mother, Grace, and Lenore's mother, Ducey. Now the only two women left in the Evans family, Luna and Lenore are left rudderless in the wake of the most Godawful Mess to date. But when the full moon finds another victim, it's clear their trouble is far from over. Now Lenore, Luna, and the new sheriff-their biggest ally-must dig deep down into family lore to uncover what threatens everything they love most. The body count ticks up, the most unexpected dead will rise-forcing Lenore and Luna to face the possibility that the undead aren't the only monsters preying on their small town"--